How many digital minds can dance on the streaming multiprocessors of a GPU cluster? - Shiller, Derek (Synthese, 2025)
Some of the technical details of the implementation of modern AI systems raise novel questions about computational functionalism. In particular, GPU clusters processing large language models often interweave the computations for many different chat responses. If the computations underlying these language models were to give rise to consciousness when run in isolation, it is not clear what to make of their status when they are interwoven. This paper draws on debates in the personal identity literature to present two alternative options, one in which many minds can be interwoven in one GPU cluster, and one on which at most a single mind can exist. Each position is coherent and it is not clear how to resolve the central issues. This is likely to be a source of further uncertainty about consciousness in production AI setups.